2011
DOI: 10.1021/jp2041026
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characteristics of Cobalt Phthalocyanine Complexes Adsorbed on Graphene

Abstract: We investigate, at a density functional level, the electric characteristics of 18 complexes of cobalt phthalocyanine (CoPc) and cobalt tetraaminephthalocyanine (CoTAPc) adsorbed on graphene functionalized with CO 2 À or CO moieties. Three models of graphene molecules are used, pristine, defect, and vacancy, leading to 12 complexes with CO 2 À functionalized graphene and 6 complexes with functionalized CO graphene. The molecular structures of the optimized complexes feature covalent adsorption CoÀO lengths of ∼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 89 publications
4
32
0
Order By: Relevance
“…15,18,23 Besides, the interaction between TMPc and supports also can affect the HOMO of TMPc, which probably improve the TMPc catalytic activity for ORR. 29,39 In common with other work, our results reveal that CuPc is beneficial to degradation of H 2 O 2 . 25 Combined with our theoretical analysis and other theoretical explanation, even if the high ΔETM-OO is detrimental to holding the two O atoms, the proper R TM-N of CuPc could lead the linear N-Cu-N structure conveniently to drag the two H atoms away by the two N atoms.…”
Section: Catalyst Evaluation By Dftsupporting
confidence: 90%
See 1 more Smart Citation
“…15,18,23 Besides, the interaction between TMPc and supports also can affect the HOMO of TMPc, which probably improve the TMPc catalytic activity for ORR. 29,39 In common with other work, our results reveal that CuPc is beneficial to degradation of H 2 O 2 . 25 Combined with our theoretical analysis and other theoretical explanation, even if the high ΔETM-OO is detrimental to holding the two O atoms, the proper R TM-N of CuPc could lead the linear N-Cu-N structure conveniently to drag the two H atoms away by the two N atoms.…”
Section: Catalyst Evaluation By Dftsupporting
confidence: 90%
“…The use of the LANL2DZ has been successfully applied in the past for other transition metals. 29 In order to evaluate the reliability of calculation method, the structures of TMPc were all optimized, and the calculated properties of optimized TMPc are listed in Table S1. The calculated distances R TM-N , which stands for bond length between the central metal atom and the nearest neighbouring N atom, are mainly investigated to prove the reliability of the calculation method.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…Kuraoka et al reported an increase in selectivity, but a decrease in permeability with CoPc supported porous glass. Formation of a superoxide adduct between O 2 and CoPc has also been reported . Shoji et al showed a continuous increase in selectivity with Co(II) porphyrin complex loading, in a Nafion membrane.…”
Section: Literaturementioning
confidence: 87%
“…The same modeling was used with success for complexes containing phthalocyanines . I‐V curves calculated at the M06/6‐31G(d,p) level of theory showed that the complexes with N‐doped graphene present the maximum current in the direction P → G, followed by complexes with B‐doped and PHP‐doped graphene.…”
Section: Quantum Chemical Studies and Potential Applicationsmentioning
confidence: 99%
“…The same modeling was used with success for complexes containing phthalocyanines. [32][33][34] I-V curves calculated at the M06/6-31G(d,p) level of theory showed that the complexes with N-doped graphene present the maximum current in the direction P ! G, followed by complexes FIGURE 1 Molecular structure of porphine indicating the three positions for substitution FIGURE 2 Electrostatic potential mapped onto total electronic density for two applied bias voltages.…”
Section: Molecular Electronicsmentioning
confidence: 99%